The Impact of the Two Infographics Types in Terms of Presentation on Developing the Cognitive and Performance Aspects of Digital Graphics Design Skills and Motivation Towards them among Students of Educational Technology at The University of Jeddah - Hosam Abdulhameed Althibyani (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
The aim of this research is to reveal the effect of the interaction between the two types of Infographics in terms of presentation (static, motion) in developing digital graphics design skills and motivation towards it among undergraduate students in the Department of Educational Technology, College of Education, University of Jeddah, Saudi Arabia. To achieve this, the experimental method was used, and the research was applied to a sample of 109 students, who were divided into four experimental groups according to the infographic technique used in education. The study reached a number of results, the most important of which is the absence of statistically significant differences at the level (α < 0.05) between the two types of Infographics in terms of presentation method (static, motion) in the development of cognitive aspects and performance aspects of digital graphic design skills and motivation towards them among students of Educational Technology in experimental groups at the University of Jeddah. In addition, there were no statistically significant differences at the level (α < 0.05) between the two types of Infographics in terms of presentation (static, motion) in developing motivation towards digital graphics among students of Educational Technology in experimental groups at the University of Jeddah. In light of these results, the research recommended the necessity of employing infographic technology in its fixed and mobile modes in teaching the digital graphics course and other courses, and in presenting the cognitive and performance structure of the course content to students, because of its significant impact on the development of performance and cognitive skills and raising the efficiency of education compared to traditional methods.